2011
DOI: 10.1186/1742-4690-8-80
|View full text |Cite
|
Sign up to set email alerts
|

Expression and reactivation of HIV in a chemokine induced model of HIV latency in primary resting CD4+ T cells

Abstract: BackgroundWe recently described that HIV latent infection can be established in vitro following incubation of resting CD4+ T-cells with chemokines that bind to CCR7. The main aim of this study was to fully define the post-integration blocks to virus replication in this model of CCL19-induced HIV latency.ResultsHigh levels of integrated HIV DNA but low production of reverse transcriptase (RT) was found in CCL19-treated CD4+ T-cells infected with either wild type (WT) NL4.3 or single round envelope deleted NL4.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 57 publications
5
92
0
Order By: Relevance
“…This paradoxical observation, in the context of a lentivirus otherwise shown to infect nondividing cells, has been puzzling. The factor(s) controlling infection in resting T cells has not yet been completely elucidated, but recent studies indicate important roles for cellular c-Jun N-terminal kinase (47) and chemokine-induced changes in the actin cytoskeleton (48). The role of the PI3K pathway in HIV infection of primary T cells is somewhat controversial, as early studies, performed in transformed cell lines and activated T cells, reported that PI3K negatively impacts HIV-1 transcription (48), whereas later work found that PI3K signaling is required for HIV integration in chemokine-treated quiescent CD4 + T cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…This paradoxical observation, in the context of a lentivirus otherwise shown to infect nondividing cells, has been puzzling. The factor(s) controlling infection in resting T cells has not yet been completely elucidated, but recent studies indicate important roles for cellular c-Jun N-terminal kinase (47) and chemokine-induced changes in the actin cytoskeleton (48). The role of the PI3K pathway in HIV infection of primary T cells is somewhat controversial, as early studies, performed in transformed cell lines and activated T cells, reported that PI3K negatively impacts HIV-1 transcription (48), whereas later work found that PI3K signaling is required for HIV integration in chemokine-treated quiescent CD4 + T cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…This has motivated the use of latency models, such as primary resting CD4 + T cells that have been infected with HIV in vitro (6)(7)(8). The kick-and-kill paradigm gained traction when it was demonstrated that latency reversal (kick) alone, with the LRA vorinostat, was insufficient to cause the death of infected cells in a postactivation in vitro latency model, whereas the addition of expanded HIV-specific CD8 + T cells resulted in infected cell elimination (5).…”
Section: Introductionmentioning
confidence: 99%
“…We generated latently infected cells with WT replication-competent HIV-1 viruses, X4 tropic NL4-3, and the R5 tropic J32228M4, as these recapitulate physiological in vivo infections. The chemokine-dependent Lewin in vitro latency model we applied for our study is well characterized (34,35,60,61) and its utility has been verified by other groups (36,58). In this model, pretreatment of resting CD4 T cells with the CCR7 ligand CCL19 has been demonstrated to promote efficient nuclear localization and integration of HIV-1 into the genome at levels similar to CD4 T cells primed for infection with PHA stimulation (34,60), recapitulating postintegration latency.…”
Section: Discussionmentioning
confidence: 96%
“…CD4 T cells from normal and HIV-1-infected PBMCs were isolated via negative selection (StemCell Technologies). CD4 T cells were cultured at 4 × 10 6 /ml in RPMI 1640 medium supplemented with 10% FBS, 100 IU/ml penicillin, 100 μg/ml streptomycin, and 20mM L-glutamine (Wisent), 0.5 ng/ml IL-7 (R&D Systems), and 25-100 nM CCL19 (R&D Systems) for 2 days prior to infection, modified from the Lewin model (34)(35)(36)60). p24 virus (1 ml of 30 ng/ml) was layered on 100 μl of a 2 mM EDTA, 20% sucrose solution in PBS (Wisent) and centrifuged at 21,000 g for 45 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation